Decision Support System For Governor Of Student Executive Board Governor (BEM) Selection Using The TOPSIS Method - Lili Suryati (Institute of Computer Science (IOCS), 2022)
The application of Decision Support System (DSS) is basically motivated by the challenges and needs of an organization to provide a system that can assist them in making the right decisions. The selection of the Governor of the Student Executive Board (BEM) can also be done with the help of the SPK. The purpose of implementing this DSS is to help select from many existing candidates into a number of candidates that will be chosen by students. If done without the help of DSS then this will require a lot of resources. The Technique for Order Performance of Similarity to Ideal Solution (TOPSIS) method is very appropriate for this purpose. TOPSIS has the principle that the chosen alternative must have the shortest distance from the positive ideal solution and the farthest distance from the negative ideal solution. The criteria that will be used in this research are GPA, number of seminar and workshop certificates, assessment of vision and mission, and initial support. The results showed that the TOPSIS method could be used to assist the selection process for the Governor of BEM.